Assessment of Anammox process against acute and long-term exposure of ZnO nanoparticles - AKGÜL, DENİZ (ELSEVIER, 2020)
The impacts of nanoparticles (NPs) on wastewater treatment have become a great concern because of their widespread applications. Although the acute responses of anammox bacteria to NPs have enhanced the knowledge about the potential risks of them, deep understanding of the cumulative impacts of NPs must be assessed. The purpose of this research was therefore to further extend the current knowledge by evaluating both acute and long-term effects of Zinc oxide (ZnO) NPs on Anammox process based on nitrogen removal performance, self-recovery ability and microbial community structure. The acute exposure tests indicated that, the median inhibition concentration (IC50) of ZnO NPs on Anammox process was 84.7 mg/L (54.82 mg ZnO NPs/g VSS). Acute exposure of 200 mg/L ZnO NPs (117.54 mg Zn/g VSS) caused 80% inhibition in batch assays while the long-term inhibition dosage was 100 mg/L ZnO NPs (187.50 mg ZnO NPs/g VSS) corresponding to 1022 mg/L total Zn (1916.27 mg Zn/g VSS) in the reactor due to the accumulation of NPs. Total, soluble and biomass-associated Zn concentrations were measured throughout the long-term exposure to observe the behavior of ZnO NPs in the reactor. Total Zn in the reactor was cumulatively increased and mostly originated from biomass-associated Zn. Following the long-term inhibition tests, self-recovery of Anammox process within 120 days demonstrated that, the ZnO NPs inhibition is reversible for the applied dose. Furthermore, next generation sequencing results indicated a symbiotic relationship between the microbial groups in the anammox bioreactor while relative abundance of Candidatus (Ca.) Brocadiaceae family showed a decrease parallel to the deterioration in nitrogen removal performance of bioreactor. At the end of the long-term exposure studies, 48.76% decline on anammox quantity was detected. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Anammox; ZnO NPs; Inhibition; Nitrogen removal; Next generation sequencing; WASTE-WATER TREATMENT; EXTRACELLULAR POLYMERIC SUBSTANCES; ZINC-OXIDE NANOPARTICLES; ACTIVATED-SLUDGE; MICROBIAL COMMUNITY; PROCESS PERFORMANCE; TIO2 NANOPARTICLES; ENGINEERED NANOPARTICLES; AG NANOPARTICLES; GRANULAR SLUDGE